Reassessing Journalist and Media Dynamics for Sustainable Development in Africa - Gana, Stephen Victor; Uzah, Terna Thomas; Inobemhe, Kelvin (Pancasila International Journal of Applied Social Science, 2025)
This study reassessed the role of journalists and media dynamics in promoting sustainable development in Africa, specifically examining how media ownership structures, profit-driven models, and government policies impact journalistic objectivity and coverage of development issues. The research employs a descriptive survey design with a population comprising journalists and media practitioners and a sample size of 30 respondents from the region. Data was collected through a structured questionnaire, with mean and standard deviation used to analyse responses. Findings showed that media ownership often influences editorial content, with ownership structures limiting journalists' independence in covering sustainable development objectively. Additionally, profit-driven models significantly affect the quality and focus of development reporting, as the pursuit of revenue frequently prioritises entertainment over critical sustainable development topics. Government policies and censorship further restrict media freedom, impeding the balanced and thorough reporting of politically sensitive development issues. Based on these insights, the conclusion reached was that structural reforms and policy interventions are necessary to enhance the media's role in sustainable development advocacy. Recommendations include promoting editorial independence, diversifying funding sources to reduce reliance on commercial revenue and implementing policies to protect press freedom and enable objective reporting on development issues across Africa.